Forest resources of Texas - Graham, J. Olin (My University, 1908)
Introduction: Within the state of Texas the natural conditions on which depend the range and make-up of the forest are of the most diverse character. In geographical position its southernmost point lies almost in the edge of the Tropics, while its far northern portions are within the wheat and corn belt of the Middle Western States.
Citation: Graham, J. Olin. Forest resources of Texas. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Forests; Texas; Trees; Forestry; Graduating theses; Senior theses; Theses